A NEW TECHNIQUE OF STRETCHABLE CONDUCTIVE SENSOR DEVELOPMENT FOR SOFT ACTUATOR DEFORMATION APPLICATION - MOHD MUSTAPHA, NURUL HASYIMAH (2024)
Application of soft robots, such as soft pneumatic actuator (SPA), has been widely explored in various fields, including rehabilitation and agriculture. It has been reported that SPA experienced elongation during motions after air pressure was supplied to the actuator from the pneumatic system. However, an in-depth study is necessary to correctly measure SPA elongations, which may be affected by unsuitable material, complex measurement methods, and inaccurate readings when using a conventional ruler. These issues have brought this study to further the evaluation of the conductive stretchable sensor performance to measure SPA elongation. Although this method has been investigated earlier, their comparison is limited to 6% and 18% of spandex fabric composition. Besides considering more on the spandex composition of the stretchable fabric during the sensor development, this study highlighted some additional parameters such as suitable pattern and the fabric conditions when stitching the conductive thread to the stretchable fabric (in course or wales direction). Then, the sensor fabrication is conducted by manipulating the different types of conductive thread, positions of the conductive thread, and the number of conductive thread lines on the stitches before undergoing tensile testing. After that, the sensor evaluation is continued with repetitive tensile testing and the sensor application on the soft actuator deformation. The best sensor was made up of fabric with 20% spandex fabricated using thread 2 in two lines of conductive thread stitched along the course direction at position 1 and position 2. The result from the repetitive testing of the best sensor showed a high linearity accuracy of 93.29% which give advantage in predicting elongation reading. At the final stage, the developed sensor has been tested on soft pneumatic actuator (SPA). Based on the test, the sensor can detect the elongation of the SPA by 25.04 mm when the SPA is pressurised with 55kPa. The formulation obtained from the elongation experiment was also validated by a manual measurement using a flexible curve ruler which gives 25.00 mm with 0.16% error. Therefore, the developed sensor offered a simple method for obtaining elongation readings for SPA deformation, which may eventually be employed as a wearable device to help measure soft items or movements such as fingers, elbows, and knees for osteoarthritis patients.